Philosophical foundations of medical law - Campos, Thana Cristina de; Herring, Jonathan; Phillips, Andelka Matija (Oxford, United Kingdom Oxford University Press, 2019)
with advances in personalised medicine, the field of medical law is being challenged and transformed. The nature of the doctor-patient relationship is shifting as patients simultaneously become consumers. The regulation of emerging technologies is being thrown into question, and we face new challenges in the context of global pandemics. This volume identifies significant questions and issues underlying the philosophy of medical law. It brings together leading philosophers, legal theorists, and medical specialists to discuss these questions in two parts. The first part deals with key foundational theories, and the second addresses a variety of topical issues, including euthanasia, abortion, and medical privacy. The wide range of perspectives and topics on offer provide a vital introduction to the philosophical underpinnings of medical law.
Virtue ethics and medical law Robert Gay -- Feminism, ethics of care, and medical ethics Jonathan Herring -- The natural law foundations of medical law Robert P George and Christopher O Tollefsen -- Consequentialism and the law in medicine Julian Savulescu and Dominic Wilkinson -- Justice and responsibility : a deontological approach to medical law Thana C de Campos -- Abortion, feminism, and "traditional" moral philosophy Kate Greasley -- How the philosophy gets in Jesse Wall -- Virtue theory and the lawfulness of withholding or withdrawing treatment or care David Albert Jones -- Dignity in medical law Charles Foster -- The beginning and ending of life : medical law and ethical incoherence John Keown -- Proportionality in medical law Francisco J Urbina -- Priority setting, judicial review, and procedural justice Daniel Wang and Benedict Rumbold -- Philosophy and restrictions on access to assisted reproductive technologies Imogen Goold -- Abortion on the basis of a risk of disability : the parents' interests and shared interests Heloise Robinson -- Property in the body and medical law Donna Dickenson -- Trafficking, tourism and trading : a dark convergence in transplantation? Trevor Stammers -- How can a reformed surrogacy law reflect pragmatism and respect ethics? Kirsty Horsey -- Ageing and fertility : legal and ethical perspectives Pia Jolliffe and William Jolliffe -- The emergence of family care agreements in an ageing world Pip Coore -- The problem of mental capacity in self-harming egosyntonic disorder Camille Kong -- Medical privacy and big data : a further reason in favour of public universal health-care coverage Carissa Véliz -- The age of personalized medicine, from patients to consumers : the digital environment, clickwrap contracts, and implications for autonomy Andelka M Phillips.
Series statement from dust jacket.
Includes bibliographical references and index.
Keywords: Medical ethics. -- Electronic books; Medical laws and legislation -- Philosophy